Correction: Ahmad et al. Estimating the Total Volume of Running Water Bodies Using Geographic Information System (GIS): A Case Study of Peshawar Basin (Pakistan). Sustainability 2022, 14, 3754 - Ahmad, Naveed; Khan, Sikandar; Ehsan, Muhsan; Rehman, Fayaz Ur; Al-Shuhail, Abdullatif (Sustainability, 2022)
The authors would like to make the following corrections to the published paper [...]